Political Connections and Firm Value in China: An Event Study - Liu, Feng (Journal of business ethics, 2018)
On 19 October 2013, the Chinese government issued the Opinions on Further Regulation on Party and Political Leaders and Cadres Working Part-Time (Holding Office) in Enterprises, also known as the 18th Decree, to regulate government officials’ employment with businesses. The 18th Decree is widely perceived as having had a significant impact on the use of independent directors with political backgrounds by firms, given the prevalence of this business practice. This paper examines the market reaction to the 18th Decree to ascertain the value effect of political connections in China. We note a negative relationship between the political connections of independent directors and market reaction. We also note that the negative relationship between political connections and market reaction is moderated by ownership type and state of regional development. Specifically, we find that the negative relationship holds only for private firms in less developed regions. These results support our prediction that political connections add value to Chinese firms and that the value effect of political connection is contingent on institutional factors.